2001
DOI: 10.2527/2001.7982134x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus bioavailability, growth performance, and nutrient balance in pigs fed high available phosphorus corn and phytase.

Abstract: Three experiments were conducted to evaluate P bioavailability, growth performance, and nutrient balance in pigs fed high available P (HAP) corn with or without phytase. The bioavailability of P in normal and HAP corn relative to monosodiumphosphate (MSP) for pigs was assessed in Exp. 1. In a randomized complete block design, 96 pigs (average initial BW 9.75 kg) were fed eight diets for 28 d. The reference and test diets were formulated by adding P as MSP, HAP, or normal corn at 0, 0.75, or 1.5 g/kg to a corn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
59
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 0 publications
17
59
2
1
Order By: Relevance
“…Phytase supplementation significantly reduced faecal P excretion in both dry and liquid fermented diets (Table 6) and similar results were reported by other authors (Näsi, 1990;Cromwell et al, 1995;Sands et al, 2001). However, the effect of phytase on total P excretion may be diverse, depending on the dietary concentration of available P. In our previous study using P-adequate diets we found that the phytase-induced reduction in faecal P excretion was partly counteracted by an increased urinary P excretion.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Phytase supplementation significantly reduced faecal P excretion in both dry and liquid fermented diets (Table 6) and similar results were reported by other authors (Näsi, 1990;Cromwell et al, 1995;Sands et al, 2001). However, the effect of phytase on total P excretion may be diverse, depending on the dietary concentration of available P. In our previous study using P-adequate diets we found that the phytase-induced reduction in faecal P excretion was partly counteracted by an increased urinary P excretion.…”
Section: Discussionsupporting
confidence: 74%
“…The results of experiments studying the effect of phytase on Ca digestibility in pigs are controversial. Some reports showed no effect (Yi et al, 1996;Harper et al, 1997;Sands et al, 2001) while others showed that phytase increased both ileal (Traylor et al, 2001) and total tract (Kemme et al, 1997) Ca digestibility. There are even studies demonstrating a greater effect of added phytase on Ca digestibility than on P digestibility (Johnston et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon entering the small intestine, phytase is quickly deactivated by rising pH or degraded by intestinal proteases (Kemme et al 2006). Values for P digestibility in the current trial are similar to those obtained in a previous trial that fed diets containing low-phytate corn to starter pigs (Sands et al 2001). The lack of a significant response in P digestibility with the addition of phytase during Phase II in the current trial, however, conflicts with previous observations in studies where pigs were fed dry cornand soybean-meal-based diets (Han et al 1997;Zhang et al 2000).…”
Section: Apparent Total Tract Digestibilitysupporting
confidence: 71%
“…Transgenics has been used to develop low-phytate plants such as soybean meal [37], high available P corn [38] and canola seeds expressing a phytase gene [39] for inclusion in swine and poultry diets. Hill et al [37] fed growing pigs a diet containing low-phytate corn and soybean meal, and the total P digestibility increased from 34 to 48% compared to a conventional corn-soybean meal diet.…”
Section: Management and Genetic Manipulation Of Feedmentioning
confidence: 99%